The use of satellite measurements (Sentinel 3) in the characteristics of the surface urban heat island in Łódź - Siedlecki , Mariusz; Górowski , Jan (Acta Geographica Lodziensia, 2024)
The study presents the results of the assessment of the surface urban heat island in Łódź based on satellite detection using the Sentinel 3 satellite. To achieve the objectives of the work, 30 selected satellite images of surface temperature from 2021–2022 were used. The study of the average urban heat island, its maximum value and spatial distribution was carried out separately for the summer (April–September) and winter (January–March) periods. The results showed that the median SUHI value was 2.6°C in the summer and 1.9°C in the winter months.